Evolution of Union Wages and Determinants - Tony Fang; John Hartley (Institute of Labor Economics (IZA), 2022)
Labor unions, chiefly through collective organizing and bargaining, almost universally increase the wages of their members, even after controlling for individual, job, firm, and other characteristics that affect pay (Fang and Verma 2002). This earnings advantage of union workers is known as the union wage premium. The premium differs by country, industry, worker, and the estimated wage premium varies by study methodology, among other factors. This chapter explains the premium's determinants and charts how they have changed over time, leading to a typically reduced wage effect in recent years relative to decades past. Such changes include globalization, technological change and a rise in the skill premium, a shift toward the service industry, less favorable labor law, and possibly increased opposition toward unions. Methodological challenges and empirical techniques are reviewed, and premium estimates by country/region are presented. An average union wage premium of 0-20% is found based on recent research, with considerable variation depending on the methodology and country under study. The literature focuses on several developed countries, and is limited in a number of developing nations, with data availability being the primary reason. Results from the developing world exhibit more variation, but often fall in line with those from developed countries such as the United States.
Keywords: J31; J33; J51; 330; union; wage differential; determinants